Welcoming remarks: Symposium on Strategy & Transformation Management For Tertiary Education / Prof. Dr. Nor Hayati Saad - Saad, Nor Hayati (2023)
In an era marked by rapid technological advancements, shifting societal needs, and an ever-changing economic landscape, the importance of strategic planning and effective management in tertiary education cannot be overstated. SSTM-TEd 2023 serves as a vital platform for us to exchange ideas, share best practices as well as collaborate on innovative strategies that will shape specifically UiTM towards the 2025 Globally Renowned University, and other institution of higher learning (IHL) at national and international level.